2022
DOI: 10.1039/d2cc00383j
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free synthesis of gem-difluorinated heterocycles from enaminones and difluorocarbene precursors

Abstract: A cascade strategy to synthesis of gem-difluorinated 2H-furans from reactions of BrCF2CO2Et with enaminones has been described. The reactions work efficiently for a broad of substrate scope and tolerates varies...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…39 In 2022, we further demonstrated that BrCF2CO2Et 11, as a unique fluorinated carbene precursor, could efficiently react with enaminones to deliver fluorinated heterocycles (Scheme 5, a). 40 The reaction could proceed in completely transition metal-free conditions, and installed a gem-CF2 functional group into the 2H-furan rings 12. The procedure is simple and easily handled and well-tolerate a wide of substrate scope (Scheme 5, b).…”
Section: Cleavage Of Enamine C-c Double Bonds and Cyclized To 2h-furansmentioning
confidence: 99%
“…39 In 2022, we further demonstrated that BrCF2CO2Et 11, as a unique fluorinated carbene precursor, could efficiently react with enaminones to deliver fluorinated heterocycles (Scheme 5, a). 40 The reaction could proceed in completely transition metal-free conditions, and installed a gem-CF2 functional group into the 2H-furan rings 12. The procedure is simple and easily handled and well-tolerate a wide of substrate scope (Scheme 5, b).…”
Section: Cleavage Of Enamine C-c Double Bonds and Cyclized To 2h-furansmentioning
confidence: 99%
“…[9] Among these building blocks, enamines or difluoroalkyl compounds are widely used compounds, especially in the field of cyclization strategy for constructing valuable heterocyclic compounds. [10][11][12][13][14][15][16] For example, Jiang's [12] group reported a novel cascade process for accessing 3,3-difluorinated 2H-furans via CÀ C bond cleavage of aminocyclopropane intermediates, generated in situ from ethyl bromodifluoroacetate and enaminones under mild conditions (Scheme 1a, right). Later on, Wan's [13] and Song's [14] group described base-promoted formal [4 + 1] cycloaddition reactions from ethyl bromodifluoroacetate and enaminones to 2,2-difluorinated 2H-furans, respectively (Scheme 1a, left).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, one of the important missions of organic synthesis is realizing the conversion of easily available, simple bulk chemicals into high value‐added products [9] . Among these building blocks, enamines or difluoroalkyl compounds are widely used compounds, especially in the field of cyclization strategy for constructing valuable heterocyclic compounds [10–16] . For example, Jiang's [12] group reported a novel cascade process for accessing 3,3‐difluorinated 2 H ‐furans via C−C bond cleavage of aminocyclopropane intermediates, generated in situ from ethyl bromodifluoroacetate and enaminones under mild conditions (Scheme 1a, right).…”
Section: Introductionmentioning
confidence: 99%
“…5 Recently, Feng's group constructed five-membered cyclic difluoroethers by Lewis acid-catalyzed [3 + 2] cycloaddition. 3 d Jiang's group reported a method for the construction of gem -difluorinated 2 H -furans with enaminones and difluorinated reagents, and the cyclopropane intermediate was proposed in the reaction 6 (Fig. 1B, left).…”
mentioning
confidence: 99%
“…First of all, electron-rich double bonds in the substrate may interact with the in situ generated difluorocarbene, 8 rendering the same products as Jiang's work. 6 Secondly, the direct interaction between tertiary amines and difluorocarbene might occur to generate quaternary ammonium salt intermediates, which will lead to formamides via further C–N bond cleavage and hydrolysis. 7 b ,9 Therefore, it is a huge challenge to construct the target products smoothly.…”
mentioning
confidence: 99%